The use of maqasid al-shari’ah between methodological and liberal approaches: some critical reflection - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas (LexisNexis, 2021)
Maqasid of the Shariah is about understanding the end-goals and purposes of both individual rulings and overall sum-total of the Shariah laws. In the mind of its original expounders, maqasid of the Shari’ah both at foundation and level of operation as a means of legal deduction is bound by the framework and parameters of the Quran and Sunnah. In contemporary time, however, this proposition has been questioned by some segments who tend to advocate the laissez-faire use of maqasid al-Shari’ah to understand and construct Islam and its various systems. To their critics, this is a lopsided approach to maqasid of the Shariah which dilutes not only the religio-ethical nature of law-making in Islam but has the potential of desacralising Islam and its legal system. Using content analysis method, this article argues that Islamic methodology of legal construction does not admit any disconnect between maqasid of the Shariah and its roots in the legal texts of the Qur’an and the Sunnah.